Análise de convergência dos parâmetros estabelecidos por meio das ferramentas de gestão do padrão ISO à indução do desenvolvimento sustentável nas organizações - Merlin, Fabrício Kurman (2011)
Dealing on sustainable development covers a set of issues involving demands from different society´s segments. The organizations are part of an environment in which they are increasingly being pressed to meet these demands and, consequently charged that their development shall be carried out sustainably. In an attempt to meet them, organizations make use of various management tools, among which, one of the most used are the ISO`s standards. Although there is evidence of contributions provided by these standards in the literature for the organization, due to its characteristics and implications of its use in the organization´s elements, it is questionable whether its parameters converge for a possible induction of sustainable development in organizations. This work presents a theoretical study, designed on the structuralism world view, descriptive and deductive method, which aims to analyze the convergence of the parameters of the management tools of the ISO`s standards for possible induction of sustainable development in the organization. In order to support the analysis, a generic framework for possible convergence was developed, based on the systems approach, linking five ISO`s standards (ISO 9001, ISO 14001, OHSAS 18001, ISO 31000 and ISO 26000) with sustainable development and positioning them according to organization levels (institutional, tactical and operational). The structure was designed based on the concept of sustainable development formalized by the Brundtland report and was submitted to experts for legitimacy. The analysis was performed exploring the generic framework for possible convergence in the lens of Nadler and Tushman model. The results provided by the analysis found that the standards can contribute to a possible induction of sustainable development in organizations, as long as they meet certain minimum conditions, related to its strategic alignment in organizations.